The enhancement of electrochemical capacitance of biomass-carbon by pyrolysis of extracted nanofibers. (20th February 2017) - Deng, Libo; Zhong, Wenhua; Wang, Jubei; Zhang, Peixin; Fang, Haoming; Yao, Lei; Liu, Xuqing; Ren, Xiangzhong; Li, Yongliang
Graphical abstract: Abstract: Biomass-derived carbons have been extensively researched as electrode material for energy storage and conversion recently. However, most of the previous works convert crude biomass directly into carbon and the electrochemical capacitances for the resultant carbons are quite often underestimated as well as large variations in capacitances exist in literatures due to the complex nature of biomass, which practically hinder their applications. In this work, polysaccharide nanofibers were extracted from an inexpensive natural fungus using a hydrothermal method and were converted to porous carbon nanofibers (CNFs) by potassium hydroxide activation. The porous carbons were assembled into symmetric supercapacitors using both potassium hydroxide and an ionic liquid (IL) as electrolytes. Solid state nuclear magnetic resonance characterization showed that the micropores of the as-prepared carbons are accessible to the IL electrolyte when uncharged and thus high capacitance is expected. It is found in both electrolytes the electrochemical capacitances of CNFs are significantly higher than those of the porous carbon derived directly from the crude fungus. Furthermore, the CNFs delivered an extraordinary energy density of 92.3 Wh kg −1 in the IL electrolyte, making it a promising candidate for electrode materials for supercapacitors.